2018
DOI: 10.1039/c7nr05499h
|View full text |Cite
|
Sign up to set email alerts
|

Upconverting nanocomposites with combined photothermal and photodynamic effects

Abstract: Lanthanide-doped upconverting nanoparticles (UCNPs) have been studied for diverse biomedical applications due to their inherent ability to convert near-infrared (NIR) excitation light to higher energies (spanning the ultraviolet, visible, and NIR regions). To explore additional functionalities, rational combination with other optically active nanostructures may lead to the development of new multimodal nanoplatforms with theranostic (therapy and diagnostic) capabilities. Here, we develop a nanocomposite consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 45 publications
(44 reference statements)
0
46
0
Order By: Relevance
“…Under 980 nm irradiation, plasmonic and UC NPs are simultaneously excited leading to a plasmonic enhancement of the UC luminescence and a simultaneous temperature increasing. Upon laser irradiation, and after loading a Zn phthalocyanine photosensitizer into the mesoporous SiO 2 , the UC visible light subsequently activates the photosensitizer to release reactive oxygen species …”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 99%
“…Under 980 nm irradiation, plasmonic and UC NPs are simultaneously excited leading to a plasmonic enhancement of the UC luminescence and a simultaneous temperature increasing. Upon laser irradiation, and after loading a Zn phthalocyanine photosensitizer into the mesoporous SiO 2 , the UC visible light subsequently activates the photosensitizer to release reactive oxygen species …”
Section: Luminescent Thermometers Based On Ln3+ Ionsmentioning
confidence: 99%
“…With the modified surface with folic acids, the hybrid structures were tested for the treatment of OECM-1 oral cancer cells via PTT and cell imaging. In 2017, Huang et al [ 63 ] also observed the upconversion emission enhancement and photothermal property in Au NR@SiO 2 @UCNPs nanocomposites with integrated functionalities, including bioimaging and PTT. Meanwhile, the photosensitizer, zinc phthalocyanine (ZnPc), was introduced into the nanocomposite and excited by the visible light generated from the UCNPs, thereby triggering the release of reactive oxygen species for application in the PDT of cancers.…”
Section: Plasmon-enhanced Upconversion Luminescencementioning
confidence: 99%
“…Compared with the traditional treatment, NIR-triggered phototherapy produces a trend with non-invasion that can be classified into photothermal therapy (PTT) 9-11 and photodynamic therapy (PDT) 12-16. The nanocomposite is more useful than the single material because the former can be tuned flexibly with multiple applications and different purposes, thereby creating a complete theranostic nanoplatform 17-21. Gold nanorod (AuNR) is commonly used for PTT and show good thermal generation via luminous energy 22.…”
Section: Introductionmentioning
confidence: 99%